The Career Thoughts Inventory and Incarcerated Males: a Preliminary Psychometric Review - Meyer, Jill M. (American journal of criminal justice, 2016)
Objective The main purpose of this preliminary study was to examine use of the Career Thoughts Inventory with male inmates. Previous research discussed within this manuscript demonstrates the link between vocational training and reduced recidivism rates of ex-offenders. Design Participants ( N = 86) who were incarcerated at a Southeastern, US prison completed the following assessments: the Career Thoughts Inventory (CTI), My Vocational Situation, the Balanced Inventory of Desirable Responding, and a short demographic questionnaire. Reliability and validity of the CTI were examined for appropriate use with this population. Results With a return rate of 66 %, the CTI demonstrated internal consistency, convergent validity and partial discriminant validity for use with incarcerated males. Future recommendations for use of the CTI with inmates, direction for career education, and research are discussed.